Unveiling the Potential of Extracellular Vesicles as Biomarkers and Therapeutic Nanotools for Gastrointestinal Diseases - Valentina Arrè; Rita Mastrogiacomo; Francesco Balestra; Grazia Serino; Federica Viti; Federica Rizzi; Maria Lucia Curri; Gianluigi Giannelli; Nicoletta Depalo; Maria Principia Scavo (MDPI AG, 2024)
Extracellular vesicles (EVs), acting as inherent nanocarriers adept at transporting a range of different biological molecules such as proteins, lipids, and genetic material, exhibit diverse functions within the gastroenteric tract. In states of normal health, they participate in the upkeep of systemic and organ homeostasis. Conversely, in pathological conditions, they significantly contribute to the pathogenesis of gastrointestinal diseases (GIDs). Isolating EVs from patients' biofluids facilitates the discovery of new biomarkers that have the potential to offer a rapid, cost-effective, and non-invasive method for diagnosing and prognosing specific GIDs. Furthermore, EVs demonstrate considerable therapeutic potential as naturally targeted physiological carriers for the intercellular delivery of therapeutic cargo molecules or as nanoscale tools engineered specifically to regulate physio-pathological conditions or disease progression. Their attributes including safety, high permeability, stability, biocompatibility, low immunogenicity, and homing/tropism capabilities contribute to their promising clinical therapeutic applications. This review will delve into various examples of EVs serving as biomarkers or nanocarriers for therapeutic cargo in the context of GIDs, highlighting their clinical potential for both functional and structural gastrointestinal conditions. The versatile and advantageous properties of EVs position them as promising candidates for innovative therapeutic strategies in advancing personalized medicine approaches tailored to the gastroenteric tract, addressing both functional and structural GIDs.